Nyeri Orofasial Sebagai Salah Satu Nyeri Alih Dari Iskemia Miokardium - Monica Dewi Ranggaini (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Referred pain on the orofacial structures can be diagnostically challenging for the dentists. Dental pain, which is the most common pain in the orofacial structures, is commonly resolved with satisfactory result, However, some dental pain can have a non-odontogenic characteristics which originate from myocardial ischemia. Myocardial ischemia symptoms may be presented as angina pectoris specific pain, but also as trigeminal pain, with or without angina pectoris symptoms. When this occurred, an improper diagnostic can lead to unnecessary dental treatment and delayed of myocardial ischemia treatment which can lead to myocardium infarct.